Experimental study on adsorption and wettability alteration aspects of a new chemical using for enhanced oil recovery in carbonate oil reservoirs. (September 2016) - Joonaki, Edris; Erfani Gahrooei, Hamid Reza; Ghanaatian, Shima
Highlights: A new chemical compound is synthesized with purpose to heavy oil EOR. Laboratory tests are conducted to study the effect of new chemical on oil recovery. Wettability alteration aspects of synthesized chemical are studied. Adsorption amount of introduced chemical compound is measured. Abstract: There is increasing interest in new multi-purpose chemicals for EOR in carbonate reservoirs, because of their oil wet nature that prevents oil from being produced. A new chemical compound [Et3 NH]Cl/1.5 AlCl3 ( X = 0.6) modified with CuCl, is developed for enhancing the recovery of the free imbibition and core flooding mechanisms for naturally fractured reservoirs. Laboratory experiments have been conducted to understand the injection of such chemical into oil-wet, fractured reservoirs. The compound is tested on Iranian heavy oil sample from the Bangestan reservoir, Marun oil field. Core plugs were prepared and aged in the crude to attain restored state samples. It is found that ionic liquid compound significantly reduces oil viscosity, molecular weight and also alters wettability to a more desirable state. This chemical compound has the capability of reducing IFT and contact angle. These combined effects result in noticeable free water imbibition recovery enhancement in Amott cell after oil has undergone a reaction with the compound. The potential of the new chemical compound for increasing oil recovery and in situ upgrading of heavy oil are also examined at reservoir condition by core flooding experiments. In addition, the adsorption behavior of the new proposed chemical is also studied.